2005
DOI: 10.1002/ddr.20003
|View full text |Cite
|
Sign up to set email alerts
|

In vitro permeation of diclofenac sodium from novel microemulsion formulations through rabbit skin

Abstract: In order to increase topical penetration of the nonsteroidal anti-inflammatory drug, diclofenac sodium, new microemulsion formulations were prepared to increase drug solubility and in vitro penetration of the drug. The influence of dimethyl sulfoxide and propylene glycol were also investigated as enhancers on the in vitro penetration of diclofenac sodium using Franz diffusion cells using excised dorsal rabbit skin. Factorial randomized design was performed to analyze the results of in vitro permeation studies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…19 Park and Kim offered 2 explanations for the decrease in droplet size with the addition of the drug: (1) a certain portion of undissolved drug acts as an emulsifying agent by the deposition of drug particles at the interface of M, or (2) the deposition of drug at the interface of M causes reduced surfactant mobility, which decreases the particle size of drug-loaded microemulsions. 23 The solubility of DS in distilled water has been previously found to be 99 mg/mL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Park and Kim offered 2 explanations for the decrease in droplet size with the addition of the drug: (1) a certain portion of undissolved drug acts as an emulsifying agent by the deposition of drug particles at the interface of M, or (2) the deposition of drug at the interface of M causes reduced surfactant mobility, which decreases the particle size of drug-loaded microemulsions. 23 The solubility of DS in distilled water has been previously found to be 99 mg/mL.…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of DS was determined spectrophotometrically at 277 nm. 18,19 Determination of n-Octanol-Distilled Water Partition Coefficient n-Octanol phases were saturated with distilled water for at least 24 hours before the experiment. A solution of DS (10 −4 M) was prepared with distilled water.…”
Section: Determination Of Drug Solubilitymentioning
confidence: 99%
“…The cleaned skin was washed with distilled water and stored in the deep freezer until further use. The skin was brought to room temperature and cut into 2 cm diameter circular patches when used (Kantarci et al, 2005;Soliman et al, 2010).…”
Section: Evaluation Of the Optimized Lacidipine Proniosomal Gel Formumentioning
confidence: 99%
“…The incorporation of chemical enhancers (dimethyl sulfoxide and propylene glycol) in w/o microemulsions resulted in enhanced topical penetration of diclofenac sodium when compared with microemulsions without enhancers [88] . Flux through rabbit skin was improved for the enhancer/microemulsion formulations compared with commercially available gel formulations, but their effect was dependent on the choice of cosurfactant (propanol or isopropanol).…”
Section: Anti-inflammatory Drugsmentioning
confidence: 99%
“…osteoarthritis) as an alternative route to overcome the adverse side effects associated with the oral and rectal routes of administration, including gastrointestinal intolerance. In the literature, several reports have shown that microemulsions represent promising vehicles for improving the delivery, efficacy and bioavailability of several NSAIDs, such as ketoprofen [41,44] , celecoxib [84] , rofecoxib [85] , aceclofenac [86] , piroxicam [87] , and diclofenac [88][89][90] . For example, Rhee et al evaluated the efficacy of microemulsions prepared with oleic acid, Labrasol/Cremophor RH 40 and water for dermal delivery of ketoprofen through rat skin [44] .…”
Section: Anti-inflammatory Drugsmentioning
confidence: 99%